2013
DOI: 10.1007/s10973-013-2994-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of calorimetry as a main tool in evaluation of the effect of carbonate additives on cement hydration

Abstract: Calorimetry was applied to follow the hydration in the Portland cement-dolomite-limestone mixtures.In the experiments the limestone additive of various fineness (standard component of various common cements), as well as the dolomite additive (not a standard component) were used. The rate of hydration versus time for common cements reflects the proper setting and early hardening during the first days after mixing with water (two or three peaks and the induction period between them). The aim of measurements pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
(10 reference statements)
2
11
0
Order By: Relevance
“…Addition of fly ash more distinctly retards the acceleratory period of cement hydration than slag, this tendency is especially clear for the high substitution rate of fly ashes. This retarding effect of the mineral additions on the cement hydration has been already reported [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Addition of fly ash more distinctly retards the acceleratory period of cement hydration than slag, this tendency is especially clear for the high substitution rate of fly ashes. This retarding effect of the mineral additions on the cement hydration has been already reported [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Resultssupporting
confidence: 68%
“…For composite binders containing fly ash, the hydration heat evolution has been studied, inter alia, by Nocuń-Wczelik [25][26][27], Pacewska et al [28][29][30], Giergiczny [31,32], Han et al [22], Kumar et al [33], Narmluk et al [34] and Mounanga et al [35]. Similarly, as for slag cements, the tests showed that the evolved heat decreases with increasing amount of fly ash addition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are frequently used in case of studies of hydration processes of cement in the presence of different additives (e.g. [37][38][39][40][41][42]). They are also useful in case of investigations of hydration/activation processes of high and very high volume fly ash mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of hydration process in the mixtures of cement with limestone powder, dolomite powder and limestone -dolomite additive were reported by Nocuń-Wczelik et al [6]. In the pastes hydrating with fine grained dolomite powder the crystallization of products is accelerated and as a consequence the strength development is improved.…”
Section: Introductionmentioning
confidence: 96%